Investigation of the Photon Strength Function in 130 Te. Issue 1 (January 2016) - Isaak, J; Beller, J; Fiori, E; Glorius, J; Krtička, M; Löher, B; Pietralla, N; Romig, C; Rusev, G; Savran, D; Scheck, M; Silva, J; et al.
Abstract: The dipole strength distribution of 130 Te was investigated with the method of Nuclear Resonance Fluorescence using continuous-energy bremsstrahlung at the Darmstadt High Intensity Photon Setup and quasi-monoenergetic photons at the High Intensity γ-Ray Source. The average decay properties were determined between 5.50 and 8.15 MeV and compared to simulations within the statistical model.